Big boots to fill : the next generation continuing differently - Clinton, Eric, (SAGE Knowledge. Cases., 2017)
This case history describes the challenge facing Carlos Garcia, the third-generation successor of a Spanish family business, as he takes over the reins of Hispalis and prepares to continue the business differently. In two generations, Hispalis has morphed into a global conglomerate, with a portfolio of business ventures in multiple industries and countries. The case history facilitates discussion of business and family issues and is appropriate for beginning-level undergraduate students in the areas of entrepreneurial leadership, family business, strategic management and corporate governance.